Fluorinated Polyurethanes, Synthesis and Properties - Olga Smirnova (Molecules, 2016)
Fluorinated polyurethanes with a glass transition temperature as low as −139 °C and a decomposition onset temperature of 247–330 °C were prepared by a reaction of fluorinated alcohols with aromatic and cycloaliphatic diisocyanates in solution or melt.